Effects of energy source on methionine utilization by growing steers - G.F. Schroeder; M.S. Awawdeh; D.P. Gnad; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2005)
We evaluated the effect of energy source on amino acid utilization in growing steers. Ruminally cannulated Holstein steers (372 lb) were limit-fed (4.2 lb/day dry matter) a diet based on soybean hulls. A 2 x 5 factorial arrangement of treatments was used: 0 or 3 grams/day of methionine and five sources of energy. The energy sources evaluated were infused in amounts of 1.3 Mcal ME/day and included: control (none), glucose (0.79 lb/day), fat (0.33 lb/day), acetate (0.85 lb/day), and propionate (0.59 lb/day). Acetate and propionate were infused continuously into the rumen, whereas glucose and fat were infused into the abomasum. Nitrogen balance was increased by methionine supplementation, indicating that this amino acid limited protein deposition. Energy supplementation also increased nitrogen balance, with or without supplemental methionine, without differences among energy sources. The results of our study suggest that amino acid utilization by growing steers is improved by energy supplementation, regardless of the source of energy.
Keywords: Cattlemen& #x27; s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Methionine; Growing steers